New Straits Times, 1 Julai 2007 - Prabhakaran S. Nair (The New Straits Times Press (M) Bhd, 2007)
Tunku had the knack of using humour to defuse awkward situation, putting people around him at ease and enabling members of his cabinet to discuss and solve the most intricate problems in a creative manner